Longibelus gen. nov., a new Cretaceous coleoid genus linking Belemnoidea and early Decabrachia. (11th September 2013) - Fuchs, Dirk; Iba, Yasuhiro; Ifrim, Christina; Nishimura, Tomohiro; Kennedy, William J.; Keupp, Helmut; Stinnesbeck, Wolgang; Tanabe, Kazushige; Sigwart, Julia
Abstract The phylogenetic origin and the timing of origination of the Decabrachia are controversial. This is due to a poor understanding of character complexes relating to the shell, which causes difficulties in establishing homologies among different taxa. One central problem concerns a clear differentiation between belemnoids and early spirulids. A comparative analysis of shell structures of well‐preserved specimens including types and new material of Cretaceous spirulids Groenlandibelus, Naefia and Cyrtobelus, as well as selected taxa of aulacocerid, belemnitid and diplobelid belemnoids, revealed a set of 14 characters. Seven characters (apical angle, chamber length, dorsal and ventral sutures, orientation of septa, direction of the dorsal part of the septal neck, primordial rostrum) are not or less diagnostic, whereas the seven remaining characters can be reliably used to distinguish between the Decabrachia on the one hand and Belemnitida and Aulacocerida on the other hand. These diagnostic characters are as follows: (1) presence/absence of a mural flap; (2) position of the siphuncle; (3) shape of the dorsal soft tissue attachment scar; (4) presence/absence of tabular nacre in the conotheca; (5) presence/absence of a rostrum proper; (6) presence/absence of a narrow rod‐like proostracum; and (7) presence/absence of a caecum. Diplobelida and 'Naefia' matsumotoi, however, exhibit a mosaic of decabrachian and belemnoid characters. Owing to striking differences between N. neogaiea, the type species of Naefia, and 'N.' matsumotoi, the new genus Longibelus has been erected. Besides a redescription of Longibelus ('Naefia') matsumotoi, we describe the first Maastrichtian occurrences of this species from Hokkaido (northern Japan) and Alaska. Among the type material of N. neogaiea from the Maastrichtian of Chile, we found one specimen that unambiguously belongs to Longibelus gen. nov. Similarly, two specimens from the Maastrichtian of Mexico previously determined as N. neogaiea also belong to the new genus. Also, we can reinterpret material from the Cenomanian of India as Longibelus gen. nov. New material from the Albian of India likewise assignable to Longibelus is described for the first time. Finally, we introduce the first records of coleoids from Zululand (South Africa). These specimens belong to Longibelus as do specimens from the Aptian of Caucasus (previously described as 'Naefia' kabanovi). A phylogenetic approach suggests that Longibelus gen. nov. is derived from diplobelid‐like belemnoids and gave rise for the Decabrachia or at least groenlandibelid spirulids. This strongly supports earlier ideas on a close relationship between Cretaceous Decabrachia and belemnites and simultaneously challenges opinions that Decabrachia originated in the Carboniferous.